A nationwide study on the incidence of mesenteric ischaemia after surgery for rectal cancer demonstrates an association with high arterial ligation. (20th May 2019) - Sörelius, K.; Svensson, J.; Matthiessen, P.; Rutegård, J.; Rutegård, M.
Abstract: Aim: The incidence of mesenteric ischaemia after resection for rectal cancer has not been investigated in a population‐based setting. The use of high ligation of the inferior mesenteric artery might cause such ischaemia, as the bowel left in situ depends on collateral blood supply after a high tie. Method: The Swedish Colorectal Cancer Registry was used to identify all patients subjected to an abdominal resection for rectal cancer during the years 2007–2017 inclusive. Mesenteric ischaemia within the first 30 postoperative days was recorded, classified as either stoma necrosis or colonic necrosis. Multivariable logistic regression was used to estimate odds ratios (ORs) with 95% confidence intervals (CIs) for mesenteric ischaemia in relation to high tie, with adjustment for confounding. Results: Some 14 657 patients were included, of whom 59 (0.40%) had a reoperation for any type of mesenteric ischaemia, divided into 34 and 25 cases of stoma necrosis and colonic necrosis, respectively. Compared with patients who did not require reoperation for mesenteric ischaemia following rectal cancer surgery, the proportion having high tie was greater (54.2% vs 38.5%; P  = 0.032). The adjusted OR for reoperation due to any mesenteric ischaemia with high tie was 2.26 (95% CI 1.34–3.79), while the corresponding estimates for stoma and colonic necrosis, respectively, were 1.60 (95% CI 0.81–3.17) and 3.69 (95% CI 1.57–8.66). Conclusion: The incidence of reoperation for mesenteric ischaemia after abdominal resection for rectal cancer is low, but the use of a high tie might increase the risk of colonic necrosis demanding surgery.